Development of Quality Rating Evaluation of Outgoing Product Case Study Applied at the General Company for Vegetable Oils (Journal of Engineering, 2013)
Research covers the uses the method of Quality Rating Evaluation to evaluate thequality of production through which a determination of product quality of its production inorder to determine the amount of sales hence the profits for the company. The most importantfunction is to satisfy consumer at reasonable prices. Methods were applied to the product(toothpaste) in the General Company for Vegetable Oil – Almaamoon Factory .The company's has obtained ISO-certified (ISO 9001-2008). Random samples offinal product intended for sale were collected from the store during months (February, April ,June , October and December) for the year 2011 to determine the "quality rating " throughthe application of the method on the products at final stage , where selected. The propertiesthat affect product quality and varieties of defects for each property (A, B, C , D) and give thepoints of on rejects .The research concluded that the percentage of output quality for the product toothpaste(AMBER) weighing 75 g ranges between (70-80%) is within quality level which is good incondition and that the company's plan was effective and influential in the development of itsproducts. In addition to the significant improvement in the level of quality and processproductivity statistically controlled and the results were within the limits of the chart qualitycontrol .Also it was found that is was within Iraqi specification (1100)